Body Weight Control by a High-Carbohydrate/Low-Fat Diet Slows the Progression of Diabetic Kidney Damage in an Obese, Hypertensive, Type 2 Diabetic Rat Model - Shuichi Ohtomo; Yuko Izuhara; Masaomi Nangaku; Takashi Dan; Sadayoshi Ito; Charles van Ypersele de Strihou; Toshio Miyata (Hindawi Limited, 2010)
Obesity is one of several factors implicated in the genesis of diabetic nephropathy (DN). Obese, hypertensive, type 2 diabetic rats SHR/NDmcr-cp were given, for 12 weeks, either a normal, middle-carbohydrate/middle-fat diet (MC/MF group) or a high-carbohydrate/low-fat diet (HC/LF group). Daily caloric intake was the same in both groups. Nevertheless, the HC/LF group gained less weight. Despite equivalent degrees of hypertension, hyperglycemia, hyperlipidemia, hyperinsulinemia, and even a poorer glycemic control, the HC/LF group had less severe renal histological abnormalities and a reduced intrarenal advanced glycation and oxidative stress. Mediators of the renoprotection, specifically linked to obesity and body weight control, include a reduced renal inflammation and TGF-beta expression, together with an enhanced level of adiponectin. Altogether, these data identify a specific role of body weight control by a high-carbohydrate/low-fat diet in the progression of DN. Body weight control thus impacts on local intrarenal advanced glycation and oxidative stress through inflammation and adiponectin levels.